(untitled) (Research, Society and Development, 2022)
This paper presents a study on the use of Information and Communication Technologies (ICTs) in the teaching and learning process of Chemistry. Given the large number the published works, the objective was sought to identify the most used tools, their contributions, and their difficulties during use. The research was carried out in the Periódicos CAPES portal and Mendeley using descriptors related to the theme. After the selection and analysis of the articles, information was extracted regarding the ICTs pointed out by the authors, as well as the benefits, possibilities, and difficulties raised by them. The search revealed a total of 355 articles published in Portuguese from 2017 to September 2021, with 55 publications included in this work. With that, 42 ICTs were listed and expressive results, positively impacting the learning process, enabling the realization of didactic and interactive work, improving the levels of motivation for students, as well as participation, and greater ownership of the new material.